Do health investments improve agricultural productivity? Lessons from agricultural household and health research - McNamara, Paul E.; Ulimwengu, John M.; Leonard, Kenneth L. (International Food Policy Research Institute, 2010)
Determining the causality between health measures and both income and labor productivity remains an ongoing challenge for economists. This review paper aims to answer the question: Does improved population health lead to higher rates of agricultural growth? In attempting to answer this question, we survey the empirical literature at micro and macro levels concerning the link between health investments and agricultural productivity. The evidence from some micro-level studies suggests that inexpensive health interventions can have a very large impact on labor productivity. The macro-level evidence at the country and global level, however, is mixed at best and in some cases suggests that health care interventions have no impact on income, much less on agricultural productivity. At both micro and macro levels, the literature does not provide a clear-cut answer to the question under investigation. Overall, the review reveals a great deal of heterogeneity in terms of estimation methods, definition and measurement of health variables, choice of economic outcomes, single-equation versus multiple-equation approach, and static versus dynamic approach. The actual magnitude of estimated elasticities is difficult to assess in part due to estimation bias caused by the endogeneity of health outcomes. We also found significant gaps in the literature; for example, very little attention is given to demand for health inputs by rural populations and farmers.